Effects of active–sterile neutrino mixing during primordial nucleosynthesis - Civitarese, Enrique Osvaldo (2014)
In the present work, we discuss the effects of the inclusion of sterile–active neutrino oscillations during the production of primordial light-nuclei. We assume that the sterile neutrino mass-eigenstate might oscillate with the two lightest active neutrino mass-eigenstates, with mixing angles ϕ1 and ϕ2. We also allow a constant renormalization (represented by a parameter (ζ)) of the sterile neutrino occupation factor. Taking ζ and the mixing angles as free parameters, we have computed distribution functions of active and sterile neutrinos and primordial abundances. Using observable data we set constrains in the free parameters of the model. It is found that the data on primordial abundances are consistent with small mixing angles and with a value of ζ smaller than 0.65 at 3σ level.